Dyeing using Pulverized Mangosteen husk and Sepang wood on Cotton and Silk - Faiz, F.A; Kheng, J.N.S (Universiti Malaysia Sarawak (UNIMAS), 2011)
The traditional way of natural dyeing is a complex process that lacks in convenience in terms of preparation and storage as fresh plant materials need to be processed immediately. Dried plant materials are expected to have a better shelf life and it would be more convenient if the plants are pulverized into powder form. This paper highlights an on-going research to evaluate the dyeing and colour shades of pulverized Mangosteen husk and Sepang wood on cotton and silk. Two sachets containing the powder of each plant sample were boiled separately and only one sachet was left to stay in the dye bath. The dyeing experiments were carried out using alum mordant. It was observed that the shades of the fabrics dyed with the sachet that remained in the dyebath were more vibrant. The Mangosteen produced light brownish-yellow shades, while the Sepang wood produced deep red shades. Finally, the Shibori technique was used to create textile design to highlight the interesting textured effects of natural colours instead of the direct dyeing that only produced a flat coloured fabric.